APLIKASI 3D VIRTUAL REALITY SEBAGAI MEDIA PENGENALAN KAMPUS POLITEKNIK NEGERI INDRAMAYU BERBASIS MOBILE - Firman Setiawan Riyadi; A. Sumarudin; Munengsih Sari Bunga (Lembaga Penelitian dan Pengabdian Masyarakat - Universitas Teknologi Digital Indonesia, 2017)
Campus promotion and introduction by some institutions in general still using the media images or print media, as is often done by State Polytechnic Indramayu in introducing and providing campus information is still using print media and images such as brochures or banners. Therefore, an application is required that can introduce and provide information about the campus, especially in the State Polytechnic Indramayu and provide information on existing buildings on campus using Virtual Reality technology. With the Virtual Reality technology is able to provide real information and can interact directly with the environment and buildings that exist in the campus although the appearance of the building and the environment still looks low poly. By setting up a smartphone that already supports or already support the Gyroscope sensor and set up Google CardBoard or VRBox glasses, users can directly use 3D virtual reality applications and can directly play it, but the effect of using this application can cause the user a bit dizzy because not used to using it. 3D Virtual Reality application is created by using software Unity, Blender, and C # programming language. The features available in this app are VR start, select building, how to use VR, and about VR. 3D virtual reality applications can be used by the State Polytechnic Indramayu as a medium of introduction Mobile-based campus that has a responsive display that can be run on smatrphone that already supports Accelerometer sensor. Gyroscope sensor, and Android operating system.